Analisis Video Wawancara Fenomena Solo Wedding pada Mayarakat Jepang - Nabiilah Putri Tarigan; Rani Arfianty (WIDAI Japanese Journal, 2023)
A wedding is a sacred event that is generally carried out by a couple, where they make a sacred promise before God to live together for life. But the solo wedding trend emerged in Japan and continues to grow until it is increasingly accepted among women aged 20-30 years. Solo wedding is a concept where women celebrate marriage without a partner. They will wear wedding dresses, have a photo session and experience a wedding similar to traditional ceremonies. In this research, a qualitative approach was used to explore the phenomena surrounding solo weddings. The researchers collected data through listening and note-taking techniques. Researchers will watch video interviews, collect data and then record the data for analysis. The collected data was then analyzed using reduction and grouping techniques. The research results show that there are 8 reasons why Japanese women choose to have solo weddings, 1) want to experience wearing a wedding dress 2) increase self-confidence 3) get married at a late age and to take photos 4) because they feel happy 5) having children 6) happier alone 7) too tired from work and 8) want to retake wedding photos.